Role of CT imaging in addressing resectability issues in differentiated thyroid cancer: imaging-based Mahajan grading system for TI and ETE - Mahajan, Abhishek; Rastogi, Shivam; Shukla, Shreya; Agarwal, Ujjwal; Vaish, Richa; Chakrabarty, Nivedita; Ashtekar, Renuka; Deokar, Shonal; Shaikh, Atif; Pai, Prathamesh; Chaturvedi, Pankaj; Ghosh Laskar, Sarbani; et al. (Frontiers in Oncology, 2024)
Background and objectiveExtrathyroidal extension (ETE) is the term used to describe the growth of the primary thyroid tumor beyond the thyroid capsule. ETE is a critical prognostic marker for thyroid tumors, necessitating accurate preoperative assessment. This study aims to evaluate the diagnostic performance of computed tomography (CT)-based grading for ETE and tracheal invasion (TI) for preoperative prediction in patients with differentiated papillary thyroid carcinoma (PTC) and compare the diagnostic accuracy with ultrasound (US).Materials and methodsThis retrospective study was approved by our institutional review board. Preoperative US and CT were performed for 83 patients who underwent surgery for PTC between 1 January 2010 and 31 December 2020. The US and CT features of ETE and TI of each case were retrospectively and independently investigated by two radiologists. The diagnostic performances of US and CT, including their specificity, sensitivity, positive predictive value (PPV), and negative predictive value (NPV) for ETE, and their accuracy in predicting ETE and TI were analyzed. As per the grading for ETE on USG and CT, lesions were graded into three grades and Mahajan grading was also devised on CT to predict the TI and graded into four grades.ResultsThe accuracy and specificity of CT are relatively good for identifying tumor infiltration into the adjacent structures and range from 82% to 87% and 95% to 98%, respectively. It, however, has a low sensitivity, between 14.3% and 77.78%, when compared to US, which suggests that in case of any doubt regarding CT evidence of tumor infiltration into surrounding structures, additional clinical examination must be performed. CT showed better sensitivity (78%) and specificity (75%) in detecting TI compared to previous studies. The diagnostic accuracy of CT Mahajan grading was 91.5% with p <0.005 in the prediction of TI.ConclusionPreoperative US should be regarded as a first-line imaging modality for predicting minimal ETE, and CT should be additionally performed for the evaluation of maximal ETE. The specificity and PPV of CT are higher than those of US in detecting overall ETE and TI of PTC. The US- and CT-based grading systems have the potential to optimize preoperative surgical planning.